2012
DOI: 10.3390/plants1020061
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny of Cirsium spp. in North America: Host Specificity Does Not Follow Phylogeny

Abstract: Weedy invasive Cirsium spp. are widespread in temperate regions of North America and some of their biological control agents have attacked native Cirsium spp. A phylogenetic tree was developed from DNA sequences for the internal transcribed spacer and external transcribed spacer regions from native and non-native Great Plains Cirsium spp. and other thistles to determine if host specificity follows phylogeny. The monophyly of Cirsium spp. and Carduus within the tribe Cardinae was confirmed with native North Ame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 38 publications
0
2
1
Order By: Relevance
“…These data indicate that specialization of Cassida on C. arvense has likely arisen through a combination of the beetle tracking phylogenetically conserved traits and responding to plant resistance characters that impose selection pressures for or against host utilization. This is in contrast to the conclusion reached by Slotta et al (2012) who suggested that specialized herbivores on Cirsium and Carduus species do not follow a phylogenetic pattern, and that phylogeny does not predict host specificity. However, it should be noted that their conclusion was based only on literature records of known host associations and therefore the insect–plant associations for the bulk of species in their phylogeny are uncertain.…”
Section: Discussioncontrasting
confidence: 99%
“…These data indicate that specialization of Cassida on C. arvense has likely arisen through a combination of the beetle tracking phylogenetically conserved traits and responding to plant resistance characters that impose selection pressures for or against host utilization. This is in contrast to the conclusion reached by Slotta et al (2012) who suggested that specialized herbivores on Cirsium and Carduus species do not follow a phylogenetic pattern, and that phylogeny does not predict host specificity. However, it should be noted that their conclusion was based only on literature records of known host associations and therefore the insect–plant associations for the bulk of species in their phylogeny are uncertain.…”
Section: Discussioncontrasting
confidence: 99%
“…Finally, OTUs initially assigned to the NCBI species-level taxon “Helianthus sp. DH-2012” [ 62 ], which based on BLAST results appears related to other North Dakota Helianthus such as H . petiolaris , were re-assigned to the genus Helianthus .…”
Section: Resultsmentioning
confidence: 99%
“…Current species of Cirsium have been classified into at least 16 different genera, and its delimitation is still controversial, leading to multiple reclassifications of many Carduinae into different genera [15,[17][18][19][20]. These delimitation difficulties are confounded by (1) low phylogenetic resolution in previous studies based on nuclear ribosomal transcribed spacers (ETS and ITS), a few low-copy nuclear genes and plastid regions [17,[19][20][21][22][23][24][25]; (2) morphological convergence in response to similar environmental conditions [26,27]; and (3) hybridization as a recurrent mechanism of speciation within the tribe Cardueae [28].…”
Section: Introductionmentioning
confidence: 99%